Perilaku phubbing pada remaja: Menguji peranan kontrol diri dan interaksi sosial - Ainul Fadilah; Nindia Pratitis; Amanda Pasca Rini (INNER: Journal of Psychological Research, 2022)
Abstract This study aims to determine the relationship between self-control and social interaction with Phubbing behaviour in adolescents. This study uses quantitative research with a total if 150 subjects. The sampling technique in this study is a purposive sampling. The research sample included in this study is adolescents aged between 12 to 21 years who lived in Surabaya. Based on the calculation of the analyzed result uses multiple regression analysis obtained a correlation score of 0.859 with p=0.000 (p<0.05) means there is a significant relationship between self-control and social interaction with Phubbing behavior. Meantime, a score of -0.636 is obtained p=0.000 (p<0.05) means there is a significant negative relationship between self-control with Phubbing behavior. The correlation score is -0.201 with p=0.013 (p<0.05) means there is a significant negative relationship between social interaction with Phubbing behaviour. The result is, the higher the self-control and social interaction that adolescents have, the lower the Phubbing behavior. The effective constribution in this study is 0.737 which means the self-control and social interaction give an influence of 73.7% on Phubbing behavior. Keywords: Self-Control, Social Interaction, Phubbing, Adolescents